Analisis Pengaruh Penggunaan QRIS Konvensional dan QRIS ESB terhadap Efisiensi Pembayaran Digital pada Rumah Makan BJ di Era Digitalisasi - Wishnu Aribowo Probonegoro; Lili Indah Sari; Ardiana (JSAI (Journal Scientific and Applied Informatics), 2026)
The development of digitalization has encouraged the adoption of cashless payment systems through the Quick Response Code Indonesian Standard (QRIS) in the culinary sector, including Rumah Makan BJ. This study aims to analyze the effect of Conventional QRIS and ESB QRIS on digital payment efficiency. This research employs a quantitative approach with a sample of 122 respondents. Data were collected through questionnaires and analyzed using SPSS version 17. The partial test results indicate that Conventional QRIS has a positive and significant effect on digital payment efficiency, with a t-value of 2.802 and a significance level of 0.006 (<0.05). ESB QRIS shows a stronger influence, with a t-value of 6.029 and a significance level of 0.000 (<0.05). Simultaneously, the ANOVA test shows an F-value of 57.155 with a significance of 0.000, indicating that both variables jointly have a significant effect on digital payment efficiency. The coefficient of determination (R²) of 0.405 indicates that 40.5% of the variation in digital payment efficiency is explained by QRIS usage. These findings are consistent with previous studies on integrated digital payment systems.